Quo Vadis : Kepastian Hukum Aturan Praktik Monopoli Dan Persaingan Usaha Tidak Sehat Pada Undang-Undang Nomor 11 Tahun 2020 Tentang Cipta Kerja - Rahmadi Tektona (Komisi Pengawas Persaingan Usaha, 2022)
The Omnibus Law concept is a scheme to build the economy to attract investors and be a solution to simplify many regulations and it is hoped to create a more conducive investment climate, overcome overlapping regulations and reduce problems in the bureaucracy. Looking at the contents of the Articles of the Job Creation Law, it is known that there are substantial changes to the Law on the Prohibition of Monopolistic Practices and Unfair Business Competition relating to law enforcement on the prohibition of monopolistic practices on Indonesian business competition, changes to objections from the District Court to the Commercial Court, the abolition of the period for reading the decision on objections and cassation by the Commercial Court and the Supreme Court, the abolition of the maximum fine limit, the elimination of criminal threats for violations of monopolistic practices. The formulation of the problem is whether the legal certainty of the rules of monopolistic practice and unfair business competition in the law on job creation. The purpose of this research is to analyze legal certainty and analyze the legal implications it causes. The type of research used in this scientific paper is a normative juridical research type.